Communication parents - adolescents and family conflicts in highschool students of two public educational institutions of Comasand San Juan de Lurigancho - Chávez Santamaría, Alexandra (2019)
The objective of the research was to determine the relationship between parent -adolescent communication and family conflicts in a sample consisting of 353 school children from the 3rd to 5th year of secondary school, of both sexes with ages ranging from 14 to 17 years, from two public educational institutions located in the districts of Comas and San Juan de Lurigancho. The Parental - Adolescent Communication Scale (ECPA) of Barnes and Olson and the Family Conflict Questionnaire of Fuentes, Motrico and Bersabe were applied. The results indicated that parent - adolescent communication correlates significantly (p <0.05) and inverse with family conflicts. It is concluded that the greater the communication between parents and adolescents, the lower will be the family conflicts in the participants of the research.